التعليق على نص المادة 34 من التعديل الدستوري الجزائري لسنة 2020 - رمضاني, فاطمة الزهراء (University of Eloued جامعة الوادي, 2021)
يطرح هذا البحث مشكلة ضوابط حقوق وحريات الأفراد، فإلى أي حد توفقت اللجنة القائمة على التعديل الدستوري الجزائري لسنة 2020، بإضافة المادة الجديدة 34الجامعة؟ وهل يمكنها أن تقيد جماح السلطات الدستورية المخاطبة بأحكامها، لاسيما المشرع الذي يتمتع بالاختصاص المنفرد والسلطة التقديرية في تنظيم هذا الموضوع؟ وقد كشفت، من خلال التعليق على أحكام هذه المادة، أن صياغتها القانونية توحي بأهميتها وضرورتها في المساهمة في تعزيز ضمانات حقوق وحريات الأفراد، فقد جاءت في إطار تحسين مضمون القواعد الدستورية المتعلقة بها، وهو ما يشكل دعما وتعزيزا لممارستها، بينما قد يشكل عدم دقة بعض المصطلحات الفضفاضة المستخدمة فيها مثل النظام العام، الأمن... إلى تأويل تفسيرها مما قد ينعكس سلبا على تطبيقها، وهو ما قد ينقص من قيمتها. وانتهت إلى القول بضرورة العناية بضبط صياغتها والعمل على تنمية الوعي بأهميتها خاصة السلطات المتعلقة بها، لأن تطبيقها الأسلم والأصح يبقى رهين الإرادة السياسية الحقيقية، كما قدمنا توصيات لإثرائها. This research raises the topicof limitation over the rights and freedoms of individuals. To what extent has the committee established on the Algerian Constitutional Amendment of 2020 reconciled, by adding the new Article 34 of the League ? Can it restrict the constitutional authorities to address its provisions, especially the legislator who has sole jurisdiction and discretionary power in regulating this issue? By commenting on the provisions of this article, it has revealed that its legal formulation indicates its importance and necessity in contributing to the strengthening of guarantees of the rights and freedoms of individuals. But the loose terminology used in it such as public order, security ... to the interpretation of its interpretation, which may reflect negatively on its application, which may diminish its value. And concluded the need to pay attention to controlling its formulation and work to develop awareness of its importance, especially the authorities related to it, because its safest and correct application remains dependent on real political will, and we have also made recommendations to enrich it.
مجلد12، عدد1
Keywords: إنفراد البرلمان، حدود الحقوق، شروط القانون، مجال المادة 34، السلطة القضائية، المحكمة الدستورية.; Parliament's exclusivity; limits of rights; conditions of law; scope of Article 34; the judiciary; the Constitutional Court.